The erotic motive in literature - Mordell, Albert, 1885-1965 (Routledge library editions. Literature and sexuality, 2017)
This work, first published in 1919, is an endeavour to apply some of the methods of psychoanalysis to literature. It traces a writer's books back to the outward and inner events of their life and to reveal of their unconscious. This unconscious is largely identical with the mental love fantasies in our present and past life. Since the terms 'unconscious' and 'erotic' are almost synonymous, any serious study of literature which is concerned with the unconscious must deal impartially with eroticism.